Regularity for Semilinear Neutral Hyperbolic Equations with Cosine Families - Seong-Ho Cho; Jin-Mun Jeong (Mathematics, 2020)
The purpose of this paper is to obtain the regularity for solutions of semilinear neutral hyperbolic equations with the nonlinear convolution. The principal operator is the infinitesimal generator of a cosine and sine families. In order to show a variation of constant formula for solutions, we make of using the nature of cosine and sine families.